“Quem nos protege da bondade dos bons?”: poder judiciário, midiatização, espetáculo – a circulação do Power Point do Lula no Twitter - NATHASJE, Mab Favero (2021)
As central question the analysis of the meanings of the speeches produced about the Judiciary on Twitter, based on the acts conveyed by the actors of the justice system in the media or on social networks, Lula's Power Point was chosen as the object of study, with focus on the elements of mediatization and circulation on Twitter. The corpus was constituted by the collection carried out on the digital social network Twitter, having as criterion the minimum amount of 20 retweets and 20 likes. This investigation aims to: a) understand how media time and mediatization logics have been absorbed by the Judiciary; b) understand how the Judiciary is related to the notions of spectacle; c) observe how the discursive processes related to the Judiciary Power circulate on the social network Twitter and if appropriation and resignification of meanings occurs; and d) analyze discursively the resignification brought by memes produced from Lula's Power Point and how it reveals the processes of circulation of senses. For that, the theories about circulation are activated to understand the speeches produced. It was observed that the circulation of content occurred mainly through appropriation and resignification in the process of media circulation, in which the post acquired several meanings.